1989
DOI: 10.1677/joe.0.1200295
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the plasma concentrations of inhibin throughout the normal sheep oestrous cycle and after the infusion of FSH

Abstract: A radioimmunoassay for inhibin was developed using a peptide containing the 1-26 amino acid sequence of the N-terminus of the alpha-chain of 32 kDa porcine inhibin as immunogen, and 125I-labelled tracer. Evaluation of this assay using Sephadex column chromatography, chromatoelectrophoresis and immunoblotting confirmed that it measured all forms of inhibin present in sheep follicular fluid and was suitable for measurement of inhibin in sheep plasma. There was no evidence of the presence of free alpha-subunit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 0 publications
6
30
0
Order By: Relevance
“…After treatment with gonadotrophins, especially with FSH, the ovarian grafts showed increased inhibin production, probably in association with increased estradiol production, and this had further negative-feedback effects on mouse pituitary FSH secretion. A similar reciprocal relationship between inhibin and FSH has been observed in FSH-or eCG-treated domestic animals (McNeilly et al 1989, Kaneko et al 1992. The fact that FSH secretion was severely suppressed in mice of the eCG-3-and porcine FSH-treated groups strongly suggests that, in these groups, follicular growth is stimulated or maintained largely by exogenous gonadotrophins, not by endogenous mouse FSH.…”
Section: Discussionsupporting
confidence: 64%
“…After treatment with gonadotrophins, especially with FSH, the ovarian grafts showed increased inhibin production, probably in association with increased estradiol production, and this had further negative-feedback effects on mouse pituitary FSH secretion. A similar reciprocal relationship between inhibin and FSH has been observed in FSH-or eCG-treated domestic animals (McNeilly et al 1989, Kaneko et al 1992. The fact that FSH secretion was severely suppressed in mice of the eCG-3-and porcine FSH-treated groups strongly suggests that, in these groups, follicular growth is stimulated or maintained largely by exogenous gonadotrophins, not by endogenous mouse FSH.…”
Section: Discussionsupporting
confidence: 64%
“…To investigate this possibility further, levels of immunoactive and bioactive inhibin were compared at various stages of the cycle. Immunoactive inhibin was quantified through use of an antibody directed against the a-subunit [7], and bioactivity was determined by inhibition of FSH production by ovine pituitary cells in vitro [24]. These two measures of inhibin were in general agreement at all times except after the LH surge, when apparent secretion of immunoactive inhibin was high but that of bioactive inhibin was low (unpublished results).…”
Section: Introductionmentioning
confidence: 89%
“…According to this hypothesis, inhibin secreted by the preovulatory follicle acts in an endocrine fashion to depress the secretion of FSH while concurrently having paracrine actions allowing the preovulatory follicle to grow and differentiate in spite of the reduction in FSH concentrations. Although inhibin secretion increases [7,8] and FSH levels decrease [9] during the follicular phase in the sheep, this change in inhibin secretion does not seem to account for the fall in FSH [7]. Although the endocrine role of inhibin during this period is uncertain, evidence is accumulating to support the paracrine aspect of this hypothesis: in vitro studies in the rat [10] and human [11] have shown that inhibin enhances LHstimulated thecal androgen production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies examining the follicular origin of inhibin relied on bioassays that, although potentially confounded by the high steroid concentrations in antral fluid, showed that inhibin bioactivity was correlated with both the number of granulosa cells and their oestrogenicity (Tsonis et al 1983). Until relatively recently, the available data on the synthesis of immunoactive inhibin was limited to assays that could not differentiate between inhibin A, inhibin B and non-bioactive isoforms of inhibin (McNeilly et al 1989. Early studies using these assays in sheep also indicated that the ovarian secretion of inhibin was positively correlated with oestradiol secretion ) and that, whilst immunoactive inhibin was secreted by both small and large antral follicles, the majority of the inhibin secreted was derived from large oestrogenic follicles (Campbell et al 1991, Mann et al 1992b.…”
Section: Introductionmentioning
confidence: 99%